2016
DOI: 10.5530/jyp.2016.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Accessibility to Medicines in Primary Health Care in a Brazilian Region

Abstract: Objective: The aim with the present study was to evaluate availability and accessibility to medicines in Primary Health Care in Northeast Health District, Belo Horizonte, Brazil. Method: It was an epidemiological, descriptive and cross-sectional study, conducted in the central warehouse and in twenty Primary Health Care units. The data was collected through direct observation, in information systems and in a survey with patients. Indicators proposed by World Health Organization were used to analyze the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…About the indicator percentage of availability of key drugs, six publications that used this indicator were also found in the review. 6,9,14,18,26,33 For this indicator, publications also show an unsatisfactory result in relation to that recommended by the World Health Organization (100%). None of the articles were in agreement with the World Health Organization, but one of the studies carried out in Brazil showed an availability of medicines of 98.3%, a result very close to the recommended value.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…About the indicator percentage of availability of key drugs, six publications that used this indicator were also found in the review. 6,9,14,18,26,33 For this indicator, publications also show an unsatisfactory result in relation to that recommended by the World Health Organization (100%). None of the articles were in agreement with the World Health Organization, but one of the studies carried out in Brazil showed an availability of medicines of 98.3%, a result very close to the recommended value.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of its weaknesses would be the failure to measure all the important aspects of medication use; this requires more intensive methodologies and more comprehensive and varied data sources. Only one of the selected studies 9 it addresses other indicators that measure the availability of medicines and geographical access in primary health care units, in addition to the indicators of rational use of medicines. In this study, the availability of essential drugs varied from 100% to 60% between the time of the visit for restrictive and educational measures regarding the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations